TALENT MANAGEMENT AND DEVELOPMENT - Nurafifah Sahib; A. M. Luthfi Virgiawan; Abdul Wahab (LPPM STAI Muhammadiyah Probolinggo, 2026)
The development of globalization and digitalization has created increasingly tight competition in the business world. In this situation, the quality of human resources becomes the main factor that determines the success of an organization. This study aims to examine the concepts of talent management and talent development, the importance of implementing these two concepts in modern organizations, the challenges faced in managing talent, as well as strategies for implementing them to improve human resource quality and organizational performance. The research method used is a literature study by reviewing various relevant scientific literature. The findings show that talent management is a strategic process to attract, develop, retain, and place individuals with competencies according to organizational needs, while talent development focuses on the continuous development of employees' skills and potential. Implementing talent management and development has been proven to boost productivity, loyalty, innovation, and the organization's readiness to face changes in the business environment. However, there are some challenges, such as rapid technological advancements, competition in getting the best talent, differences in workforce generational traits, and a lack of organizational commitment to human resource development. Therefore, organizations need to apply an integrated talent management strategy through competency-based recruitment, ongoing training, effective performance appraisal systems, career planning, and building a positive organizational culture.